DETEKSI MOLEKULER EKSON 1 GEN BETA GLOBIN PADA PASIEN TALASEMIA BETA MAYOR DI RSUD DR. SOEROTO NGAWI DENGAN METODE POLYMERASE CHAIN REACTION (PCR) - Agus Supriadi; Ana Indrayati; Elfahmi Elfahmi (Jurnal Farmasi Indonesia, 2017)
Talasemia is an autosumal recessive gene mutation caused by a lack of synthesis of hemoglobin-forming globin chains of blood with anemia-like symptoms will decrease the production of red blood cells, and should be treated with regular blood transfusions.This study aims to determine the presence of mutations in exon 2 gene beta globin thalassemia patients using PCR method, where 5 samples in DNA isolation and continued PCR amplification, the amplification result of electrophoresis region 2 beta globin gene Region II is the result of amplification of primary 4 and primer primer reverse 5 with a target of 350 bp, on PCR there is amplification or doubling of the desired DNA sequence based on the primary selection for the reaction, the PCR product of each of these regions which is subsequently performed by SSCP.In the SSCP result the five samples were found in one sample showing different ribbon pattern with the sample N, there was sample 6, while the remaining four samples, there were 1,2,3,5 showed three bands. All the samples showed different from the N sample pattern. This shows that all samples indicated there were mutation